Systemic oxidant/antioxidant balance in human abdominal aortic aneurysm. (May 2016) - Menteşe, Umit; Turan, Ibrahim; Usta, Sefer; Demir, Selim; Koral, Özgür; Öztaş Menteşe, Seda; Çavuşoğlu, Ismail Gökhan; Karahan, Süleyman Caner; Alver, Ahmet; Doğan, Orhan Veli; Aykan, Ahmet Çağrı
The aim of this study was to evaluate the oxidant-antioxidant balance in patients with abdominal aortic aneurysms (AAA). Forty-two consecutive patients with AAA and 46 control subjects were included. Total oxidant status (TOS) and total antioxidant status (TAS) levels were measured and the oxidative stress index (OSI) value determined. Serum TOS and OSI values in patients with AAA were higher than those in the controls (p<0.001, p<0.001, respectively). There was a positive correlation between abdominal aortic diameters, serum TOS levels (r=0.592, p<0.001) and OSI values (r=0.598, p<0.001). A cut-off value of 17.68 µmol H2 O2 equivalent/L for TOS was associated with 86% sensitivity and 83% specificity and a cut-off value of 1.77 for OSI was associated with 86% sensitivity and 81% specificity for predicting AAA. Systemic oxidative imbalance develops in patients with AAA, particularly as a result of an increase in TOS.